Respuesta :
Answer:
The correct option is A. Distribute –4 to get –8x + 4 > 5 – 3x
Step-by-step explanation:
The inequality is given to be : –4(2x – 1) > 5 – 3x
To solve this given inequality :
STEP 1 : Distribute -4 over 2x - 1
⇒ -8x + 4 > 5 - 3x
STEP 2 : Add -4 on both the sides
⇒ -8x > 1 - 3x
STEP 3 : Add 3x on both the sides
⇒ -5x > 1
Therefore, The correct first step to solve this inequality is : Distribute –4 to get –8x + 4 > 5 – 3x
Hence, The correct option is A. Distribute –4 to get –8x + 4 > 5 – 3x